Glucagon-Like Peptide-1 and Hypothalamic Regulation of Satiation: Cognitive and Neural Insights from Human and Animal Studies - Joon Seok Park; Kyu Sik Kim; Hyung Jin Choi (Diabetes & Metabolism Journal)
Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have emerged as blockbuster drugs for treating metabolic diseases. Glucagon-like peptide-1 (GLP-1) plays a pivotal role in glucose homeostasis by enhancing insulin secretion, suppressing glucagon release, delaying gastric emptying, and acting on the central nervous system to regulate satiation and satiety. This review summarizes the discovery of GLP-1 and the development of GLP-1RAs, with a particular focus on their central mechanisms of action. Human neuroimaging studies demonstrate that GLP-1RAs influence brain activity during food cognition, supporting a role in pre-ingestive satiation. Animal studies on hypothalamic feed-forward regulation of hunger suggest that cognitive hypothalamic mechanisms may also contribute to satiation control. We highlight the brain mechanisms of GLP-1RA-induced satiation and satiety, including cognitive impacts, with an emphasis on animal studies of hypothalamic glucagon-like peptide-1 receptor (GLP-1R) and GLP-1R-expressing neurons. Actions in non-hypothalamic regions are also discussed. Additionally, we review emerging combination drugs and oral GLP-1RA formulations aimed at improving efficacy and patient adherence. In conclusion, the dorsomedial hypothalamus (DMH)—a key GLP-1RA target—mediates pre-ingestive cognitive satiation, while other hypothalamic GLP-1R neurons regulate diverse aspects of feeding behavior, offering potential therapeutic targets for obesity treatment.